2022
DOI: 10.3389/fmars.2022.1004300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of four types of mesoscale eddies in the north pacific subtropical countercurrent region – part I spatial characteristics

Abstract: The North Pacific Subtropical Countercurrent (STCC) region has high mesoscale eddy activities due to its complex circulation structure. This study divides these mesoscale eddies into four types: cyclonic cold-core eddy (CCE), anticyclonic warm-core eddy (AWE), cyclonic warm-core eddy (CWE), and anticyclonic cold-core eddy (ACE) according to the rotation direction of the eddy flow field and the sign of average temperature anomaly within the eddy after spatial high-pass filtering. CCE and ACE are called normal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…It should be noted that there are still some abnormal eddies in the SCS that cannot be detected by our method. The eddies that have negatively correlated SSH-SST relationships [63,64] may also play an important role in ocean dynamics and biogeochemical activities. These eddies are also found in the SCS [35,36], though with low frequency.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are still some abnormal eddies in the SCS that cannot be detected by our method. The eddies that have negatively correlated SSH-SST relationships [63,64] may also play an important role in ocean dynamics and biogeochemical activities. These eddies are also found in the SCS [35,36], though with low frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The method identifies the eddies' centers from geostrophic current anomaly data obtained from satellite altimeters and then obtains the eddies' boundaries, which allows for an easier and more flexible way to identify eddies within the velocity field. Numerous studies have validated this method's effectiveness, and it has been extensively utilized in various regions [33][34][35][36][37][38][39][40][41]. We detected and tracked mesoscale eddies globally using the daily average data of sea level anomaly (SLA), preserving only those with lifetimes exceeding 30 days in the results.…”
Section: Eddy Detection and Tracking Algorithmmentioning
confidence: 99%
“…From a conventional perspective, AEs/CEs are often associated with a warmer/colder cores in comparison to that of the background water mass. Nevertheless, recent studies have identified numerous abnormal eddies with opposite-temperature structures, including AEs with cold cores and CEs with warm cores (Itoh and Yasuda, 2010;Liu et al, 2021;Ni et al, 2021;An et al, 2022;Qi et al, 2022;Sun et al, 2023). In this study, these eddies are respectively named cold-core anticyclonic eddies (CAEs) and warm-core cyclonic eddies (WCEs).…”
Section: Introductionmentioning
confidence: 96%
“…An abnormal anticyclonic eddy surface, characterized by a lensshaped structure and a cold core, was investigated by 3-day insitu observations in the northern South China Sea (SCS), the conductivity-temperature-depth(CTD) and acoustic doppler current profiler(ADCP) measurements produced comprehensive information about the eddy's characteristics (Qi et al, 2022). Using eddy-resolving model data (OFES) from 2008 to 2017, a considerable amount of abnormal eddies were found to exist in the Kuroshio-Oyashio extension region and North Pacific Subtropical Countercurrent (STCC) region, and their spatial and seasonal variations have been exhaustively investigated (An et al, 2022;Sun et al, 2023). Although their definitions and detection methods of abnormal eddies are different, it can be confirmed that abnormal mesoscale eddies are ubiquitous in the global ocean.…”
Section: Introductionmentioning
confidence: 99%